PERFORMAN LAJU PERTUMBUHAN RELATIF DAN KELULUSHIDUPAN UDANG VANNAME (Litopenaeus vannamei) MELALUI SUBSTITUSI TEPUNG IKAN DENGAN SILASE TEPUNG CACING TANAH (Lumbricus rubellus) - Diana Rachmawati; Istiyanto Samidjan (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
The  objective  of  this  study  was  to  examine  the  effect  of  feeding  substitution  from  fish  meal  to earthworm  meal  silage  (Lumbricus  rubellus) and  also  to  determine  the  best  dose  of  feeding substitution  from  fish  meal  to  worm  meal  (Lumbricus  rubellus) on  relative  growth rate and survival rate of Vanname Shrimp (Litopenaeus vannamei).  Methodology used in this  study  was laboratory treatments  with complete random design.  The study consisted of  four treatments and three repetitions.  The treatments were feeding substitution from fish meal to worm meal with four different  levels  of  mix;  those  were  treatment  A  (0%  of  earthworm  meal  silage  +  100%  of  fish meal),  treatment  B  (25%  of  earthworm  meal  silage  +  75%  of  fish  meal),  treatment  C  (50%  of earthworm  meal  silage  +  50%  of  fish  meal),  and  treatment  D  (75%  of  earthworm  meal  silage  + 25% of fish  meal).  The average  weight of the Vanname shrimp used in this study ranged 1.7 ± 0.017  g/fish  with  stock  density  of  1  fish  per  liter.    The  artificial  feed  was  in  the  form  of  pellet. Feeding time was three times a day.  The results show that the substitution of feed ingredient from fish  meal  to  earthworm  meal  silage  significantly  (P<0.01)  affected  on  relative  growth  rate; however, it did not significantly (P>0.05) affect on survival rate of Vanname shrimp.  The study also shows that the best level of feeding substituion from fish meal to earthworm meal silage was at the  level  of  25%  (treatment  B).  The  water  quality  during  study  was  in  viable  range  for  the Vanname Shrimp (Litopenaeus vannamei) cultivation. Key words : Vanname shrimp, Substitution, Silage, Relative Growth, Survival Rate